2012
DOI: 10.1186/1749-8090-7-63
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal origin of internal thoracic artery from the thyrocervical trunk: surgical considerations

Abstract: An unusual case of left internal thoracic artery (ITA) origin from the thyrocervical trunk (TCT) was detected during routine cadaver dissection. The variability of origin and course of ITA has less or more frequently been documented in the literature. However, the ITA origin from the TCT on the left side has been detected less commonly, making its dissection and preparation during coronary artery bypass grafting surgery more difficult. We discuss the ITA origin and course variability as well as clinical signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…It has been suggested that a common origin of the ITA and TCT would complicate surgical grafting procedures, as the curved direction of the common trunk makes the implant vulnerable to kinking from traction in harvesting (10). Th is was not observed in our patient.…”
Section: Discussionmentioning
confidence: 54%
“…It has been suggested that a common origin of the ITA and TCT would complicate surgical grafting procedures, as the curved direction of the common trunk makes the implant vulnerable to kinking from traction in harvesting (10). Th is was not observed in our patient.…”
Section: Discussionmentioning
confidence: 54%
“…Theoretically, such variations in branching may lead to future complications such as coronary or shoulder-girdle muscle steal phenomenon and kinking of the artery during CABG. 6 However, to the best of our knowledge, no such complication has been reported in the literature. It is important to recognize variant anatomy when patients are under consideration for therapeutic interventions such as CABG to help develop safe surgical procedures.…”
Section: Discussionmentioning
confidence: 81%
“…But the presence of two separate origin of scalenus anterior muscle observed in the present study is a rare anomaly. The Internal thoracic artery is widely utilized as a great conduit for myocardial revascularization [3][4][5] and its variability in origin is of great surgical importance. A study reveals that 1% of right ITA originates from right thyrocervical trunk [6].…”
Section: Resultsmentioning
confidence: 99%